PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK PADA SEKOLAH MENENGAH PERTAMA DI SURAKARTA - Rahayu, Suryani Jati; Sukarmin, Sukarmin; Karyanto, Puguh (EDUSAINS, 2019)
PROJECT BASED LEARNING IMPLEMENTATION IN JUNIOR HIGH SCHOOL IN SURAKARTAAbstractProject-based learning needs to be implemented in junior high schools because by applying this model it will enhance student creativity. Project-based learning is a learning model that makes students active and innovative, completing a project in a certain period. This study aims to analyze the learning process at the junior high school in several schools in Surakarta to implement project-based learning. The design of this study is qualitative descriptive. Data analysis using Milles Huberman by observation, in-depth interviews, and student cognitive achievement. The results show that the learning that has been done in several Junior High School in Surakarta has not used project-based learning. This lack of using Project-Based learning is because the teacher has no direction or is still limited to learning using the Project-Based Learning model, so the teacher prefers to teach with lecture and discussion methods in the classroom. Even though in the 2013 curriculum, the application of a student-centered learning model is highly recommended. The researcher hopes that the results of this study will help design a curriculum that uses a project-based learning model. AbstrakPembelajaran berbasis proyek perlu diterapkan di sekolah menengah pertama, karena dengan penerapan model ini akan meningkatkan kreativitas siswa. Pembelajaran berbasis proyek merupakan model pembelajaran yang membuat siswa aktif dan inovatif, menyelesaikan suatu proyek dalam kurun waktu tertentu. Studi ini bertujuan untuk menganalisis proses pembelajaran tingkat SMP pada beberapa sekolah di Surakarta untuk menerapkan pembelajaran berbasis proyek. Desain penelitian ini deskriptif kualitatif. Analisis data menggunakan Milles Huberman dengan cara observasi, wawancara mendalam dan hasil belajar kognitif siswa. Hasil nya menunjukkkan bahwa pembelajaran yang telah dilakukan di beberapa SMP Negeri di Surakarta belum menggunakan pembelajaran berbasis proyek. Hal ini dikarenakan guru tidak memiliki arahan atau masih terbatas untuk pembelajaran menggunakan model Project Based Learning, sehingga guru lebih memilih mengajar dengan metode ceramah dan diskusi di kelas. Padahal di kurikulum 2013, penerapan model pembelajaran yang berpusat pada siswa sangat dianjurkan. Peneliti berharap dengan hasil penelitian ini akan membantu perancang kurikulum membuat perubahan yang berkaitan dengan pembelajaran dengan menerapkan model Project Based Learning.Â